2021
DOI: 10.3390/antibiotics10020175
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage-Derived Depolymerases against Bacterial Biofilm

Abstract: In addition to specific antibiotic resistance, the formation of bacterial biofilm causes another level of complications in attempts to eradicate pathogenic or harmful bacteria, including difficult penetration of drugs through biofilm structures to bacterial cells, impairment of immunological response of the host, and accumulation of various bioactive compounds (enzymes and others) affecting host physiology and changing local pH values, which further influence various biological functions. In this review articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 143 publications
1
59
0
Order By: Relevance
“…Biofilm formation has a great impact on bacterial physiology and survival, allowing cells to resist various deleterious environmental factors [60]. Biofilm is of great importance in the pathogenicity of many bacteria, including P. aeruginosa, making it extremely difficult to fight these bacteria [61].…”
Section: Biofilm Formationmentioning
confidence: 99%
“…Biofilm formation has a great impact on bacterial physiology and survival, allowing cells to resist various deleterious environmental factors [60]. Biofilm is of great importance in the pathogenicity of many bacteria, including P. aeruginosa, making it extremely difficult to fight these bacteria [61].…”
Section: Biofilm Formationmentioning
confidence: 99%
“…Overall, the depolymerase treatment were unable to completely inhibit or remove biofiolms and the number of viable bacterial counts in the biofilms were similar to the untreated controls [18][19][20]25], with a few exceptions [24,29]. These suggested that using depolymerases as a stand-alone treatment might not be sufficient in controlling infections associated with biofilms.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, depolymerases also present high specificity toward a narrow range of target polysaccharides (specific capsular type of the bacteria). In some cases, depolymerases might only be active against a subset of bacteria of their parent phage which are already specific to a small set of bacteria strains [18,29,36]. Such narrow host spectrum would greatly limit the wider therapeutic application of depolymerases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tail fiber (TF) with function of capsular depolymerase is another attractive virion protein. Some applications of phage-derived depolymerase have been used in penetration of bacterial cell wall, reducing impairment of immunological response, or against bacterial biofilm [22,23]. Furthermore, depolymerase therapy as an antibiotic was shown to be in robust health of mice study [24].…”
Section: Introductionmentioning
confidence: 99%